Original paperINTAKES OF SELECTED NUTRIENTS, BONE MINERALISATION AND DENSITY OF ADOLESCENT FEMALE SWIMMERS OVER A THREE-YEAR PERIOD - Czeczelewski, J.; Długołęcka, B.; Czeczelewska, E.; Raczyńska, B. (Biology of Sport, 2013)
The aim of this study was to conduct three-year monitoring of bone mineralization (BMC) and bone mineral density (BMD) of adolescent girls engaged in swimming at the time of attaining the peak bone mass and of their counterparts leading a rather sedentary life, considering the intakes of calcium, phosphorus and protein, as well as the proportions among those nutrients. Two groups of girls aged 11–13 years were studied 3 times at yearly intervals: untrained controls (n = 20) and those engaged in competitive swimming (n = 20). Bone density was determined by dual-energy X-ray absorptiometry (DXA) in the lumbar spine (L2 – L4). Nutrient intakes (energy, protein, calcium, phosphorus) were assessed from 24-h recalls. The group of swimmers had significantly lower BMI values than the control group. No systematic, significant between-group differences were found in nutrient intake or in bone mineralization variables. Calcium intake was below the recommended norm in all subjects but mean values of bone mineralization variables (BMC, BMD) steadily increased in both groups. The BMD z-scores proved negative throughout the three-year period of early adolescence in both groups of girls and that decrease was significant in swimmers. This could have been due to insufficient calcium intake as well as to inadequate calcium-to-phosphate and protein-to-calcium ratios and, when continued, might result in a decreased bone mass in adulthood.